2012
DOI: 10.1128/jb.06820-11
|View full text |Cite
|
Sign up to set email alerts
|

The PhoP/PhoQ System and Its Role in Serratia marcescens Pathogenesis

Abstract: Serratia marcescens is able to invade, persist, and multiply inside nonphagocytic cells, residing in nonacidic, nondegradative, autophagosome-like vacuoles. In this work, we have examined the physiological role of the PhoP/PhoQ system and its function in the control of critical virulence phenotypes in S. marcescens . We have demonstrated the involvement of the PhoP/PhoQ system in the adaptation of this bacterium to growth on scarce environmental Mg 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…marcescens PhoPQ has been demonstrated to control critical virulence phenotypes and be involved in the adaptation to growth with scarce Mg 2ϩ and in the presence of PB, which constitute signals to activate the PhoPQ system (27). Here we found that S. marcescens PhoP can sense both Mg 2ϩ and PB to activate the expression of ugd and arn genes, which are involved in LPS synthesis and modification.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…marcescens PhoPQ has been demonstrated to control critical virulence phenotypes and be involved in the adaptation to growth with scarce Mg 2ϩ and in the presence of PB, which constitute signals to activate the PhoPQ system (27). Here we found that S. marcescens PhoP can sense both Mg 2ϩ and PB to activate the expression of ugd and arn genes, which are involved in LPS synthesis and modification.…”
Section: Discussionmentioning
confidence: 62%
“…The ability of S. marcescens to survive the killing action of CAPs is clearly important in the pathogenesis of S. marcescens (27). Although some studies revealed that proteases and LPS modification appeared to be necessary for CAP resistance in other bacteria (3,4), the molecular mechanisms underlying the CAP resistance of S. marcescens remain totally unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PhoP regulons (i.e., the collections of genes controlled by PhoP) are widely divergent, possibly because of differences in the ecological niches occupied by bacterial species that harbor PhoP/PhoQ homologs. Nonetheless, these regulons share certain features: First, PhoP regulates expression of at least one Mg 2+ transporter gene (92), e.g., mgtA in Escherichia coli and mgtE in Serratia marscecens (5, 61). Second, the PhoP/PhoQ system positively regulates its own transcription in Salmonella (115), E. coli (61), and Yersinia pestis (92), and this seems to be conserved in other enteric species.…”
Section: Bacterial Requirements For Growth In Low Mg2+mentioning
confidence: 99%
“…The PhoP/PhoQ system is found in a wide range of gram-negative bacterial species [66-73]. Its role in governing the adaptation to low Mg 2+ conditions is conserved within the family Enterobacteriaceae [57].…”
Section: Introductionmentioning
confidence: 99%